Bayesian Phylogeographic Analysis Incorporating Predictors and Individual Travel Histories in BEAST. Issue 4 (9th April 2021) - Hong, Samuel L.; Lemey, Philippe; Suchard, Marc A.; Baele, Guy
Abstract: Advances in sequencing technologies have tremendously reduced the time and costs associated with sequence generation, making genomic data an important asset for routine public health practices. Within this context, phylogenetic and phylogeographic inference has become a popular method to study disease transmission. In a Bayesian context, these approaches have the benefit of accommodating phylogenetic uncertainty, and popular implementations provide the possibility to parameterize the transition rates between locations as a function of epidemiological and ecological data to reconstruct spatial spread while simultaneously identifying the main factors impacting the spatial spread dynamics. Recent developments enable researchers to make use of travel history data of infected individuals in the reconstruction of pathogen spread, offering increased inference accuracy and mitigating sampling bias. Here, we describe a detailed workflow to reconstruct the spatial spread of a pathogen through Bayesian phylogeographic analysis in discrete space using these novel approaches, implemented in BEAST. The individual protocols focus on how to incorporate molecular data, covariates of spread, and individual travel history data into the analysis. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Creating a SARS‐CoV‐2 MSA using sequences from GISAID Basic Protocol 2 : Setting up a discrete trait phylogeographic reconstruction in BEAUti Basic Protocol 3 : Phylogeographic reconstruction incorporating travel history information Basic Protocol 4 : Visualizing ancestral spatial trajectories for specific taxa